Synthesis and properties of a novel high-temperature vinylpyridine-based phthalonitrile polymer. (September 2019) - Wang, Haifeng; Zhang, Zhenjiang; Ji, Puguang; Yu, Xiaoyan; Naito, Kimiyoshi; Zhang, Qingxin
A novel vinylpyridine-based phthalonitrile monomer, 2, 6-bis[3-(3, 4-dicyanophenoxy)styryl]pyridine (BDSP), was resoundingly produced by a nucleophilic substitution reaction of 2, 6-bis(3-hydroxystyryl)pyridine with 4-nitrophthalonitrile in the presence of potassium carbonate. The chemical structure of the synthesized BDSP was confirmed by proton ( 1 H) and carbon ( 12 C) nuclear magnetic resonance (NMR) as well as Fourier transform infrared (FTIR) analysis. The curing behavior of BDSP was investigated by FTIR and differential scanning calorimetry (DSC) analyses. The resin showed a low complex viscosity in the wide processing window between the monomer melting temperature and the curing temperature of the polymer, as discovered by rheological analysis. In addition, the properties of the polymer were studied by thermal gravimetric analysis (TGA) and dynamic mechanical analysis (DMA). Based on the test results, the BDSP polymer demonstrated superior processing performance, excellent thermal stability, outstanding mechanical properties, and low water uptake, and these advanced performance characteristics are critical to many fields.